A transcriptome analysis of two grapevine populations segregating for tendril phyllotaxy. (12th July 2017) - Arro, Jie; Cuenca, Jose; Yang, Yingzhen; Liang, Zhenchang; Cousins, Peter; Zhong, Gan-Yuan
Abstract: The shoot structure of cultivated grapevine Vitis vinifera L. typically exhibits a three-node modular repetitive pattern, two sequential leaf-opposed tendrils followed by a tendril-free node. In this study, we investigated the molecular basis of this pattern by characterizing differentially expressed genes in 10 bulk samples of young tendril tissue from two grapevine populations showing segregation of mutant or wild-type shoot/tendril phyllotaxy. One population was the selfed progeny and the other one, an outcrossed progeny of a Vitis hybrid, 'Roger's Red'. We analyzed 13 375 expressed genes and carried out in-depth analyses of 324 of them, which were differentially expressed with a minimum of 1.5-fold changes between the mutant and wild-type bulk samples in both selfed and cross populations. A significant portion of these genes were direct cis -binding targets of 14 transcription factor families that were themselves differentially expressed. Network-based dependency analysis further revealed that most of the significantly rewired connections among the 10 most connected hub genes involved at least one transcription factor. TCP3 and MYB12, which were known important for plant-form development, were among these transcription factors. More importantly, TCP3 and MYB12 were found in this study to be involved in regulating the lignin gene PRX52, which is important to plant-form development. A further support evidence for the roles of TCP3-MYB12-PRX52 in contributing to tendril phyllotaxy was the findings of two other lignin-related genes uniquely expressed in the mutant phyllotaxy background. Abstract : Grapevine: A tale of two tendril arrangements Genetic analysis suggests an explanation for differing arrangements of tendrils on grapevine plants, with implications for grape production. Grapevines are unique in that their tendrils, which are usually modified leaves, are also the starting point for the bunches of flowers that will later become fruits. Thus, an understanding of how tendril development is controlled may provide insights into grape production. An international team led by Gan-Yuan Zhong of the USDA-Agricultural Research Service, Geneva, USA, studied a population of grape plants, some of which displayed a normal grapevine tendril arrangment relative to the leaves, and some of which showed alternative arrangements. By comparing the genes that differed in activity between the two types of grapevine, they identified key components in the genetic control of this complex trait.